Simulasi Dampak Perubahan Faktor-Faktor Ekonomi Terhadap Ketahanan Pangan Rumah Tangga Pertanian - Gatoet Sroe Hardono (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2003)
EnglishThe objective of this research is to analyze the impact of changing in economic factors on agricultural household food security, which is conducted by using simulation method. Source of the data comes from PATANAS’s research in 1999. The result shows that increasing in allocation of household resources (time allocation in labor activities and cultivated land) has positive impact on agricultural household food security. The negative impact of increasing in input prices (fertilizer and wage) could be compensated if it is followed by increasing output price proportionally. The development of household food security programs should be convergence, integrated, and give priority to wetland area since the basis of agricultural household food security in that region worse than in non-wetland area.IndonesianPenelitian ini bertujuan menganalisis dampak perubahan faktor-faktor ekonomi terhadap ketahanan pangan rumah tangga pertanian dengan metode simulasi menggunakan data PATANAS 1999. Hasil analisis menunjukkan, kenaikan alokasi sumberdaya internal rumah tangga (waktu berburuh dan luas garapan) berdampak positif terhadap ketahanan pangan rumah tangga pertanian. Dampak negatif akibat kenaikan harga-harga input (pupuk dan upah buruh tani) dapat dikompensasi bila kenaikan harga tersebut diikuti kenaikan harga output secara proporsional. Program peningkatan ketahanan pangan rumah tangga hendaknya bersifat konvergen, dilaksanakan terpadu dan memprioritaskan daerah agroekosistem sawah sebagai areal target, mengingat basis ketahanan pangan rumah tangga pertanian di daerah tersebut lebih buruk dibanding di daerah nonsawah.